第3回豪日南極研究協力ワークショップの報告 - 川口, 創; カワグチ, ソウ; 渡邉, 研太郎; ワタナベ, ケンタロウ; Kawaguchi, So; Watanabe, Kentaro (国立極地研究所, 2016)
2015年8月6-7日にタスマニア大学，海洋南極研究所において第3回豪日南極研究協力ワークショップが開催された．本ワークショップは現在すでに進行中ならびに今後4-5年内に計画されている共同研究および調査に関する情報を共有し東南極における国際的な研究効率化や研究機会の増大効果に資することにあった. 議論は，両国が共有する研究課題，プロポーザルの共同執筆，研究設備共有や多国間研究コーディネーションなど多岐にわたった． The 3rd Joint Workshop on Australian and Japanese Collaboration in Antarctic Science was held at the Institute for Marine and Antarctic Studies, University of Tasmania, Hobart, Australia on the 6th and 7th of August 2015. The primary aim of the workshop was to identify and highlight current collaborations and campaigns, and those planned for the next few years, and to share this information to maximize the synergy and opportunities for East Antarctic science within the international context. Discussion covered a range of issues including research areas of common interest, resource sharing, development of joint research proposals, multinational research coordination, and future meetings. departmental bulletin paper